Blurring the color line: racial identity construction of individuals in interracial families - Tracy, Sandy Nesbit, author; Banning, James H., advisor; Cook, Alicia Skinner, committee member; Hughes, Blanche M., committee member; Vernon, Irene S., committee member (Colorado State University. Libraries, 2005)
Stories provide meaning and challenge prevailing thinking. This interdisciplinary narrative inquiry uses lenses of feminist standpoint theories, critical race theories, family systems theory, and symbolic interactionism to select stories from twelve individuals from interracial families to tell the value of lived experience in understanding race and racial identity. The twelve participants include seven women and five men ranging in age from 23 to 67 and in educational levels from high school to Ph.D. Their racial backgrounds include African American, American Indian, Japanese American, Mexican American, and Caucasian, including mixtures of the above. They are partners, wives, husbands, parents, sons, daughters, sisters, brothers, aunts, uncles, and grandparents in families in which individuals identify with different races, through marriage, partnership, birth, and adoption. One participant is the adult daughter of the researcher. Each participant or couple is portrayed in an individual section with intercalary space, poetic representations, narratives, visual images of their hands, and a description by the researcher. A chapter on all participants' stories in different stages of harmony and cacophony compares and contrasts their stories on race, family, religion, community, work, school, historical context, adoption, and intersections of race, class, gender and sexual orientation. Participants' own words on what they want educators and community professionals to know are included. People in interracial families blur the color line that is so deeply entrenched within United States American culture. Their contexts - generation, geography, appearance, abilities, experiences, orientations, religion, families - influence their identities. They ask to be accepted, not "othered." Their stories continue their family stories in past, present, and future, speaking to a time for healing and harmony. This narrative inquiry reflects the tension of a push for traditional research according to certain formulas and a pull of feminist and borderland thinking that challenges the dominant culture. Privileging stories over numbers and questions over answers, this study invites the reader's participation.
Keywords: multicultural education; minority and ethnic groups; sociology; women's studies; families and family life; personal relationships; individual and family studies; ethnic studies